Factors influencing the health-seeking behaviors of women with advanced stages of breast cancer in Southwestern Nigeria: An interpretive description study. (2021) - Agatha Ogunkorode, Rev. Sr.; Holtslander, Lorraine; Ferguson, Linda; Maree, Johanna E.; Anonson, June; Ramsden, Vivian R.
Abstract: Background: The World Health Organization (WHO) indicates the survival rate from breast cancer in Nigerian women is 48.9%. Little is known about the health-seeking behaviors and the factors that influence women with advanced breast cancer in Southwestern Nigeria to seek care. Objectives: This paper presents the factors influencing the health-seeking activities of women with advanced breast cancer from the time the participants observed breast changes until they presented in the hospital for care. Methods: Qualitative methods, specifically Interpretive Description (ID), was employed within the conceptual framework of the Health Belief Model (HBM). A University Human Ethics Review Board (REB) approved the study, while operational approval was granted by the hospital where the data collection took place. Thirty women with advanced breast cancer were recruited for the study using purposive sampling. Data was collected by engaging the participants in audio-recorded, semi-structured, face-to-face, one-on-one interviews guided by open-ended questions and a demographic form. The interview transcripts were analyzed using thematic analysis, while the demographic information was analyzed using descriptive statistics. Results: The study identified motivating and enabling factors as well as barriers to engaging in health-seeking behaviors. Breast changes, interpretation of symptoms, the financial challenges of breast cancer treatments, sociocultural factors, and a desire to live influenced the participants' health-seeking behaviors. Conclusion: Knowledge of these factors may help nurses and other healthcare providers to consider their patients' health beliefs and perceptions, thereby empowering nurses to provide comprehensive, holistic, contextually relevant and efficient care to their patients. Community interventions should include strategies to raise breast cancer awareness and reduce the stigma associated with the illness.